Prevalence and association of hyperuricemia with liver function in Saudi Arabia: a large cross-sectional study - Abdulaziz Almuqrin; Yazeed Abdullah Alshuweishi; Mohammed Alfaifi; Hussam Daghistani; Yazeed A. Al-Sheikh; Mohammad A. Alfhili (Annals of Saudi Medicine, 2024)
BACKGROUND: Hyperuricemia is linked to an increased risk of various chronic diseases, but data on the prevalence and association of hyperuricemia with liver function in Saudi Arabia are scarce. OBJECTIVES: Evaluate the prevalence, association, and risk measures of hyperuricemia and liver function in the Saudi population. DESIGN: Retrospective, cross-sectional analysis SETTING: Database on large portion of Saudi population PATIENTS AND METHODS: Laboratory data, age, and gender of the studied subjects were collected from Al Borg Diagnostics. Subjects were stratified, based on their uric acid (UA) levels, into three groups: hypouricemic, normouricemic, and hyperuricemic. The association of UA with liver enzymes was examined in all three groups. MAIN OUTCOME MEASURES: Association of serum UA levels with alanine transaminase (ALT), aspartate transferase (AST), alkaline phosphatase (ALP), and total bilirubin (TB). SAMPLE SIZE: 13 314 subjects. RESULTS: Our study showed that the prevalence of hyperuricemia in the Saudi population is 17.3% (20.3% in males and 15.1% in females). We also found a positive correlation between ALT, AST, and TB with UA levels. The risk of being hyperuricemic was significantly increased in individuals with elevated ALT, AST, and TB. Individuals with elevated ALT, AST, and total TB had a higher chance of having hyperuricemia than those with normal activity. Notably, ALT, AST, and TB had good discriminating capacity for hyperuricemia. CONCLUSIONS: Hyperuricemia is highly prevalent in the Saudi population and is associated with compromised liver function. However, further studies are needed to elucidate the mechanisms underlying these findings in large prospective cohort studies in different populations. LIMITATIONS: Lack of data on other potential confounding variables.